Results of study on earthworms living in some covered vegetation soils of the Sonla province - Lien, Vu Thi; Kim Hoi, Huynh Thi; Canh, Le Xuan (Academia Journal of Biology, 2006)
This paper presented the preliminary study results on earthworms living in some covered vegetation soils in 3 localities: Naot (Maison district), Coma (Thuanchau district) and Chiengsinh (Sonla city) of the Sonla province. The study was carried out in three years (2002, 2003 and 2004). The samples were collected in 3 biotops (the secondary forest soil, the savanna soil and the grassland soil) at each locality. There were 21 earthworm species belonging to 7 genera of 5 families were recorded in these areas. Among these genera, Pheretima was the one which had the highest number of species (14 species-accounted for 66.7% of the total species number). Among these species, Dichogaster modigliani (Rosa, 1896) and Pheretima penichaetifeta Thai, 1984 predominated in individual number and biomass. The highest number of earthworm species was in the secondary forest soil with 12 species; the following one was in the savanna soil with 9 species and in the grassland soil with 9 species. This study showed that the species composition and the distribution of earthworms depended on the vegetation cover. The study has also showed the density and the average biomass per m2 of earthworms in these biotops.